Service quality evaluation of Islamic banks in UAE: an importance-performance analysis approach - Abduh, Muhamad; Othman, Abdallah A.M. (Islami Bank Training and Research Academy, 2014)
The landscape of modern financial institution has seen its dominance not only by conventional banks but also Islamic banking system. The intense competition brought about due to this development has earned service quality an important determinant of customer loyalty. As such this study is aimed at evaluating the service quality of Islamic banks, particularly in the UAE. The analysis is done using descriptive statistics and importance-performance analysis method. The finding shows that attributes plotted in quadrant “concentrate here” are speedy approval of financing proposal, speedy approval of opening new account, cost of services and products, and Islamic working environment. It shows that the performance of those attributes needs to be improved in order to maintain existing and attract new customers. Meanwhile, attributes plotted in quadrant “possible overkill” are internet banking and variety of the banking products. Hence, effective and efficient services are still considered as the main factors affecting customer satisfaction and bank management should wisely and carefully manage those attributes in the future.